Yoḥannǝs IV and the Patriarchate of Alexandria: Obtaining Four Coptic Bishops while Ceding Nothing on Jerusalem Issue (1876–1882) - Ancel, Stéphane (Aethiopica, 2022)
This article connects two events that occurred in 1881: the arrival of four Coptic bishops in Ethiopia and the attempt by the Copts to remodel the Dayr al-Sulṭān monastery in Jerusalem. First, connecting these two events contradicts the idea that the Copts agreed to appoint four bishops without any compensation—on the contrary they sought a compensation in Jerusalem. Second, it sheds light on Yoḥannǝs’s diplomatic policy, which enabled him to thwart the Coptic ambitions in Jerusalem and to kill two birds with one stone: he obtained four Coptic bishops, while preserving the rights of the Ethiopians in Jerusalem, and this without any compensation to be given in exchange to the Copts or anyone else. This article shows that behind a friendship demonstrated at the time by Ethiopians and Copts were hidden elements of deep discord. It therefore suggests the need, in the future, to rethink the place to be given to the 1881 agreement in the history of relations between Copts and Ethiopians and its influence on subsequent events.